Perioperative probiotics attenuates postoperative cognitive dysfunction in elderly patients undergoing hip or knee arthroplasty: A randomized, double-blind, and placebo-controlled trial - Hu, Lin; Luo, Manli; Huang, Huifan; Wu, Lanping; Ouyang, Wen; Tong, Jianbin; Le, Yuan (Frontiers in Aging Neuroscience, 2023)
Abstract Background: Postoperative cognitive dysfunction (POCD) is a common complication in elderly patients following surgery. The preventing and/or treatment strategies for the incidence remain limited. Objective: To investigate the preventive effect of perioperative probiotics treatment on POCD in elderly patients undergoing hip or knee arthroplasty. Methods: After obtained Ethics approval and written informed consent, 106 patients (age ≥ 60 years), who scheduled elective hip or knee arthroplasty, were enrolled from 16th March 2021 to 25th February 2022 into this randomized, double-blind and placebo-controlled trial. They were randomly assigned with 1:1 ratio to receive either probiotics or placebo treatment (four capsules, twice/day) from hospital admission until discharge. Cognitive function was assessed with a battery of 11 neuropsychological tests on the admission day and the postoperative day 7, respectively. Results: 96 of 106 patients completed the study and their data were finally analyzed. POCD occurred in 12 (26.7%) of 45 patients in the probiotics group and 29 (56.9%) of 51 patients in the placebo group (relative risk [RR], 0.47 [95% confidence interval [CI], 0.27 to 0.81]; P = 0.003]). Among them, mild POCD occurred in 11 (24.4%) in the probiotics group and 24 (47.1%) in the placebo group (RR, 0.52 [95% CI, 0.29 to 0.94]; P = 0.022]). No significant difference of severe POCD incidence was found between two groups (P = 0.209). Compared with the placebo group, the verbal memory domain cognitive function was mainly improved in the probiotics group. Conclusion: Probiotics may be used perioperatively to prevent POCD development and improve the verbal memory performance in elderly patients receiving hip or knee arthroplasty.